Proceedings of the 28th International Conference on Intelligent User Interfaces 2023
DOI: 10.1145/3581641.3584064
|View full text |Cite
|
Sign up to set email alerts
|

Addressing UX Practitioners’ Challenges in Designing ML Applications: an Interactive Machine Learning Approach

Abstract: UX practitioners face novel challenges when designing user interfaces for machine learning (ML)-enabled applications. Interactive ML paradigms, like AutoML and interactive machine teaching, lower the barrier for non-expert end users to create, understand, and use ML models, but their application to UX practice is largely unstudied. We conducted a task-based design study with 27 UX practitioners where we asked them to propose a proof-of-concept design for a new ML-enabled application. During the task, our parti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Context Relevance was also proposed in the context of providing Guidelines to Human-AI Interaction and maps to Show contextually relevant information in the study [3], with the difference that in Human-AI Interaction, the context is the user's inferred goals and attention during the interaction, while in our GUI ML Tools Heuristics, the context is the current dataset and problem. This becomes increasingly important when building Fair ML models as emphasized by practitioners [22]. To summarize, after conducting a usability evaluation on the prototype of the GUI ML tool that followed the newly proposed set of heuristics, it was found that fewer usability issues were present in the prototype.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Context Relevance was also proposed in the context of providing Guidelines to Human-AI Interaction and maps to Show contextually relevant information in the study [3], with the difference that in Human-AI Interaction, the context is the user's inferred goals and attention during the interaction, while in our GUI ML Tools Heuristics, the context is the current dataset and problem. This becomes increasingly important when building Fair ML models as emphasized by practitioners [22]. To summarize, after conducting a usability evaluation on the prototype of the GUI ML tool that followed the newly proposed set of heuristics, it was found that fewer usability issues were present in the prototype.…”
Section: Discussionmentioning
confidence: 93%
“…The scaffolding approach followed in iML tools allowed the users to focus their mental efforts on integrating their domain knowledge into the models. For example, Teachable Machine [12] was recently evaluated in the context of aiding the development of prototypes by UX practitioners (UXP) to propose a proof-ofconcept design for a new ML-enabled application [21]. Participants found it valuable to interactively explore different combinations of model classes and visualize the data.…”
Section: Interactive Machine Learningmentioning
confidence: 99%
“…Interactive machine teaching (IMT) is an interaction framework by which subject matter experts-who are often not experts in machine learning-draw upon their personal expertise to train machine learning (ML) models that can operate effectively within their domain [32,48,79,90,111,119]. While conventional ML is primarily concerned with developing algorithms that automatically learn conceptual representations from training data, IMT argues that learnable representations should directly come from human knowledge [79,111].…”
Section: Interactive Machine Teachingmentioning
confidence: 99%